Distribution of some heavy metals in muscle tissues of Luciobarbus xanthopterus - Düşükcan, Mustafa; Eroğlu, Mücahit; Canpolat, Özgür; Çoban, Mehmet Zülfü; Çalta, Metin; Şen, Dursun (My University, 2014)
In this study, the concentration of some heavy metals (Cu, Fe, Zn, Cr, Cd, Co and Pb) were determined in water and in the muscle of Luciobarbus xanthopterus fish to study the potential human risk of consumption and the relationship between the heavy metal load of fish and some of their biological aspects (weight, lenght and sex) and seasonal variation. Transfer Factors of heavy metals in L. xanthopterus were also determined. It was found that heavy metals accumulated in muscle tissue of L. xanthopterus were higher than that in the water. The concentration of heavy metals showed differences according to weight, length and sex of fish. The metal concentrations were determined in muscle tissue of female higher than those in male fish. The results were discussed and compared with tolerable values for heavy metals provided from the EPA, WHO, FAO and Turkish Food Codex (TFC) to determine whether this species has any risk for human consumption.

Bu çalışmada, bazı ağır metallerin (Cu, Fe, Zn, Cr, Cd, Co and Pb) su ve Luciobarbus xanthopterus’un kas dokusundaki konsantrasyonları, bu balığın insanlar tarafından tüketilmesinde bir risk oluşturup oluşturmadığı ve balıkta ağır metal birikimi ile balığın bazı biyolojik özellikleri (ağırlık, uzunluk ve cinsiyet) arasındaki ilişki belirlenmiştir. Ayrıca, L. xanthopterus’da ağır metallerin Transfer Faktörü belirlenmiştir. L. xanthopterus’un kas dokusunda biriken ağır metallerin konsantrasyonu sudan daha yüksek bulunmuştur. Ağır metal birikimlerinin balığın vücut ağırlığına, uzunluğuna ve cinsiyetine bağlı olarak değişiklik gösterdiği görülmüştür. Dişi balıkların kas dokusundaki metal konsantrasyonlarının erkek balıklardan daha yüksek olduğu tespit edilmiştir. Bu türün insanlar tarafından tüketilmesinin herhangi bir risk taşıyıp taşımadığı EPA, WHO, FAO ve Türk Gıda Kodeksi tarafından önerilen kabul edilebilir değerler ile karşılaştırılarak tartışılmıştır.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Transfer factor; Heavy metals; Muscle; Luciobarbus xanthopterus; Transfer faktörü; Ağır metal; Kas